Hubungan Pengajaran Mata Kuliah Penulisan Karya Ilmiah dengan Kemampuan Metodologi Penelitian ITA Semester 3 Grup E - Tiara Martha Lewinda Sitanggang; Ela Elia Silangit; Andar Gunawan Pasaribu (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The Scientific Writing course plays an important role in equipping students with academic skills, particularly in developing systematic and scientifically sound research methodology. This study aims to analyze the relationship between the Scientific Writing course and the research methodology writing skills of Group E Semester 3 students. The research method used is a quantitative method with a correlational approach. Data were collected through documentation and questionnaire techniques to measure mastery of the course material and students' ability to write research methodology. Data analysis was carried out using a correlation test to determine the level of relationship between variables. The results of the study indicate that there is a positive and significant relationship between the Scientific Writing course and students' research methodology writing skills. Students who have a good understanding of scientific writing materials tend to be able to develop research methodologies more systematically, logically, and in accordance with scientific principles. This finding confirms that the Scientific Writing course contributes significantly to improving students' academic competence, particularly in writing research methodology. This study is expected to be used as material for evaluating and developing scientific writing learning in higher education. The researcher distributed a questionnaire via Google Form consisting of 11 questions to group D students to obtain research results. The results of the study in the form of a questionnaire showed that 18 students (90%) felt a high level of satisfaction with the teaching of the Scientific Paper Writing course because it helped them understand the structure of research and how to write research methodology correctly and 2 students (10%) felt that it was just so-so.